Penerapan Green Accounting dan Environmental Performance Serta Pengaruhnya terhadap Profitabilitas pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI - Agung Winardi; Muhamad Firman Maulana; Muhammad Yahya; Ani Kusumaningsih (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine and analyze the impact of implementing green accounting and environmental performance on the profitability of food and beverage companies listed on the IDX during the period 2020–2024. The sample selection was conducted purposively, resulting in a total of 8 companies. The data used are secondary data obtained from the annual reports of the listed companies during the specified period. The analysis employed is panel data regression using the Random Effect Model (REM). Results analyzed with EViews version 12 indicate that the green accounting variable has a positive effect on company profitability, as it is considered a long-term investment; the capital invested now can provide a good image and long-term benefits for the company. Conversely, the environmental performance variable does not show a significant effect on profitability, despite the companies generally achieving a blue rating, which indicates efforts in environmental management in accordance with legal regulations. However, the environmental performance results have yet to guarantee a significant increase in company profitability.